Maleachi - Schart, Aaron (W. Kohlhammer GmbH, 2019)
This commentary initially outlines a synchronous view of the final canonical text of Malachi, particularly in relation to the arguments set out in the disputations. The history of the text=s origins is then reconstructed. Removing the many additions reveals an originally independent collection of disputation texts. The additions introduce clarifying details that are felt to be necessary, add motifs from other writings in the Book of the Twelve Minor Prophets, or adapt the text to changed historical conditions. Finally, attention turns beyond the text of Malachi: as the last text in the Book of the Twelve Minor Prophets, Malachi makes reference to the preceding prophetic writings. The New Testament in turn takes up Malachi=s statements and develops them further. Finally, Schart examines the theological relevance of the book and also discusses questions of objective criticism and history of interpretation, as well as current issues. Der Kommentar entwirft zunächst eine synchrone Sicht auf den kanonischen Endtext von Maleachi, insbesondere auf die Argumentation der Disputationsworte. Sodann wird die Entstehungsgeschichte des Textes rekonstruiert. Die Abhebung der vielen Zusätze bringt eine ursprünglich selbstständige Sammlung von Disputationsworten zum Vorschein. Die Zusätze bringen als notwendig empfundene Präzisierungen ein, fügen Motive aus anderen Schriften des Zwölfprophetenbuchs ein oder passen den Text an gewandelte historische Rahmenbedingungen an. Schließlich wird der Blick über die Maleachi-Schrift hinaus gerichtet: Maleachi bezieht sich als letzte Schrift des Zwölfprophetenbuchs auf die vorhergehenden Prophetenschriften. Das Neue Testament wiederum greift Aussagen Maleachis auf und entwickelt sie weiter. Schließlich untersucht Schart die theologische Relevanz des Buches und behandelt dabei auch sachkritische, auslegungsgeschichtliche und aktuelle Fragen
Keywords: Altes Testament; Dodekapropheton; Exegese; Hintere Propheten; Kleine Propheten; Kommentar; Zwölfprophetenbuch